Pemberdayaan Masyarakat Koperasi Budidaya Kambing dan Domba Guna Mewujudkan Kampung Cerdas Sosial - Agus Surono; Agung Subyakto; Suprapto; Nurlaili Humaidah; Nur Husodo; Daril Ridho Zuchrillah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Goat and sheep cultivation has traditionally been implemented from generation to generation by breeders cultivating goats and sheep in the cooperative